Digital Twin Technology for Education, Training and Learning in Construction Industry: Implications for Research and Practice - Omrany, H; Al-Obaidi, KM; Ghaffarianhoseini, A; Chang, RD; Park, C; Rahimian, F (Emerald, 2025)
Purpose: This study explores the potential of digital twin (DT) technology to enhance education and training in the construction industry. It aims to provide a clear understanding of how DT can be applied for educational purposes and proposes a framework to facilitate the adoption of DT in construction training. Design/methodology/approach: A systematic literature review was conducted to examine the current applications of DT technology in construction education and training. A total of 19 relevant studies were identified and analysed to evaluate the tools, technologies, educational objectives and integration methods used in developing DT models for the construction sector. Based on this analysis, a conceptual framework was developed to guide the integration of DT technology into construction education, addressing gaps in the current literature and practices. Findings: The analysis revealed a strong consensus on the effectiveness of DT technology in supporting education and training objectives within the construction industry. The study highlighted the fragmented nature of the current literature and proposed a comprehensive framework designed to facilitate the integration of DT in construction education. This framework offers a structured approach to bridging the gap between theoretical learning and real-world application. Originality/value: The research presents a new systematic framework developed based on an in-depth review for utilising DT in education, training and learning (ETL) processes in construction. The framework provides a novel and structured learning process to integrate theoretical knowledge with practical skills to support workforce development in the construction industry. This framework offers a structured roadmap for future research and practical applications.
Keywords: 4005 Civil Engineering; 40 Engineering; 33 Built Environment and Design; 3302 Building; 4 Quality Education; 0905 Civil Engineering; 1202 Building; 1503 Business and Management; Building & Construction; 3301 Architecture; 3302 Building; 4005 Civil engineering